Aprimoramento de técnicas parasitológicas e sorológicas para o diagnóstico da estrongiloidíase: estudo experimental e em amostras humanas de área endêmica - João Gustavo Mendes Rodrigues (2024)
Strongyloidiasis is a neglected disease caused mainly by Strongyloides stercoralis, a nematode that can persist for decades in the human host with a low parasite burden and without specific symptoms. The main obstacle to control this parasitic infection is the low sensitivity of the parasitological methods used in diagnosis and the lack of standardization and validation of immunological diagnostic alternatives. Therefore, this study aims to develop, standardize, and evaluate parasitological and serological tests to improve the sensitivity of the diagnosis of strongyloidiasis, using experimental infection of rats and human samples collected in an endemic area. The first part of the study was performed in Wistar rats infected with different burdens (10L3 or 500L3) of S. venezuelensis (Sv), treated or not with dexamethasone or ivermectin, and followed for 60 days. Fecal and blood samples were collected to evaluate the effectiveness of different parasitological methods, circulating leukocyte profiles, and the reactivity of diverse immunoglobulin isotypes. The modified Rugai technique (RMOD) showed greater sensitivity in detecting larvae in all experimental groups evaluated, especially in groups infected with low parasite burden, compared to the other parasitological techniques evaluated. The experimental infection induced a significant increase in circulating leukocytes, especially in the acute phase. The increase in circulating eosinophils was associated with the presence of the parasite, and an early reduction in these cells was demonstrated in rats infected and treated with ivermectin, confirming its relationship with active infection by S. venezuelensis. The production of IgM, IgG, and IgG1 anti-L3 and anti-Sv was elevated in all infected experimental groups regardless of the parasite burden, however, the reactivity remained elevated even after the parasitological cure. In contrast, the reactivity of IgG2a to L3 and adult worm antigens in plasma, and anti-ES/L3 IgA in the intestinal lavage was better associated with active infection, returning to the baseline levels in cured or treated animals. The second part of the study was performed with 68 individuals living in Vergel do Lago, Maceió, AL, who agreed to participate in the research and provided fecal samples for parasitological tests and blood samples for serological analysis. The diagnostic accuracy of each test was evaluated in comparison to the Consolidated Reference Standard (CRS) established using multiple parasitological tests that estimated a prevalence of 8.82% (6/68) for strongyloidiasis in the studied population. The parasitological techniques of agar plate culture (AP-C) and spontaneous sedimentation (SS) showed a sensitivity of 50% and 33.3%, respectively; while, the RMOD technique detected all infected individuals, demonstrating 100% sensitivity. The serum IgG4 anti-L3 reactivity showed the best diagnostic performance, with sensitivity and specificity of 80% and 98.3%, respectively; and also, better agreement with the CRS (kappa= 0.783). These data demonstrate that the RMOD technique and the assay based on IgG4 anti-L3 reactivity presented a better performance for detecting infection by Strongyloides spp. in individuals with low parasite burden, allowing a more sensitive diagnosis for strongyloidiasis.